Features of cystadenofibroma on magnetic resonance imaging: an update using the O-RADS lexicon and considering diffusion-weighted and perfusion imaging. Issue 154 (September 2022) - Avesani, Giacomo; Elia, Lorenzo; Anghelone, Andrea Giovanni; Perazzolo, Alessio; Panico, Camilla; Di Paola, Valerio; Gui, Benedetta; Rodolfino, Elena; Moro, Francesca; Testa, Antonia Carla; Manfredi, Riccardo
Highlights: Cystoadenofibroma has typical "dark-dark appearance" of the solid component. On Perfusion Weighted Images, solid tissue shows type I time-intensity curve. Solid tissue shows no significant restriction in Diffusion Weighted Images. O-RADS score is able to stratify the risk of malignancy in our entire sample. Abstract: Purpose: Cystadenofibroma (CAF) is a rare tumour of the ovary that can be confused with a borderline or malignant lesion due to its morphological characteristics. The study aims to analyse the MRI (magnetic resonance imaging) features of histologically proven ovarian cystadenofibromas according to lexicon-based and O-RADS (Ovarian-Adnexal Reporting and Data System) descriptors, with particular attention to time-intensity curves (TIC) and Diffusion-Weighted sequences (DWI); we also wanted to test the performance of O-RADS MRI risk stratification system in this particular subgroup of patients. Methods: We have included all patients who performed MR between October 2019 and December 2021 after an inconclusive trans -vaginal ultrasound. All patients underwent surgery with histological results of CAF. According to the O-RADS lexicon, we reported the morphological characteristics of each lesion and their appearance in the perfusion-weighted imaging (PWI) and DWI sequences. We assessed the risk of malignancy for each lesion through O-RADS MRI score. Results: Twenty-one histologically proven CAF were analysed, of which 20 benign and one borderline with degeneration into adenocarcinoma. We described the typical morphological characteristics of CAF according to lexicon-based and O-RADS descriptors. Analysis of time-intensity curves (TIC) in PWI sequences showed a slow and progressive enhancement of solid tissue (type I curve), configuring an O-RADS score of 2 or 3, except for the only malignant lesion that showed a type II curve and restriction in DWI (O-RADS 4). Conclusions: Our study is the largest comprising PWI and DWI sequences, highlighting their pivotal role. O-RADS score correctly classified the masses as benign or malignant.